2013
DOI: 10.1002/pat.3200
|View full text |Cite
|
Sign up to set email alerts
|

Study of the fire resistant behavior of unfilled and carbon nanofibers reinforced polybenzimidazole coating for structural applications

Abstract: a With increasing interest in epoxy-based carbon fiber composites for structural applications, it is important to improve the fire resistant properties of these materials. The fire resistant performance of these materials can be improved either by using high performance epoxy resin for manufacturing carbon fiber composite or by protecting the previously used epoxy-based composite with some fire resistant coating. In this context, work is carried out to evaluate the fire resistance performance of recently emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The aromatic polybenzimidazoles (PBIs) are linear heterocyclic macromolecules that belong to the class of high performance polymers, they are resistant to acids and bases, have high glass transition temperatures, excellent thermal stability and mechanical stability . Such unique combination of the properties makes them very attractive for various potential applications such as different kinds of membranes, ultrafilters, electrochemical sensors, fire‐resistant materials, among other uses.…”
Section: Introductionmentioning
confidence: 99%
“…The aromatic polybenzimidazoles (PBIs) are linear heterocyclic macromolecules that belong to the class of high performance polymers, they are resistant to acids and bases, have high glass transition temperatures, excellent thermal stability and mechanical stability . Such unique combination of the properties makes them very attractive for various potential applications such as different kinds of membranes, ultrafilters, electrochemical sensors, fire‐resistant materials, among other uses.…”
Section: Introductionmentioning
confidence: 99%
“…The initial weight loss is attributed to evaporation of moisture from PBI. 9 The thermal stability of 2.5% calcium silicate nanopowder-filled PBI film shows a stable behavior, up to a temperature of 500 C. When the percentage of calcium silicate increased to 7.5%, the thermal stability has been further increased to 590 C. This is the significance of using PBI as the coating material for increasing the thermal stability and fire resistivity of phenolic composite. 18 The high thermal stability of PBI is due to the presence of aromatic and heterocyclic rings in the backbone of the polymer chain.…”
Section: Thermogravimetric Analysismentioning
confidence: 97%
“…Due to atmospheric pressure plasma treatment on the phenolic composite surface, contact angle decreases significantly, which is a clear indication of the increase in wettability. The effect of air plasma treatment of carbon epoxy composite was studied by Ebla et al 9 and it was revealed that there was a decrease in contact angle from 72 to 17 . 9 The FTIR and AFM results reveal that there is a significant increase in hydrophilic functional groups and surface roughness on the plasma-treated surface.…”
Section: Limiting Oxygen Index Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been a lot of progress to increase the application of PBI. These applications include fiber, membranes, nano‐filtration and gas separation . Currently, commercial PBI is available in global markets as Celazole® and SCM 7000.…”
Section: Introductionmentioning
confidence: 99%